EFL teacher’s methodology and classroom management impact on second baccalaureate students’ academic performance at Unidad Educativa “Mayor Horacio Zurita Bayas”. - Barreto Barzola, Richard Moisés (2017)
This study aimed at determining the ways in which the current EFL teacher’s methodology and classroom management techniques may be contributing or not to academic performance in an EFL second baccalaureate class at Unidad Educativa “Mayor Horacio Zurita Bayas”. The data was collected through the analysis of the English records provided by the institution, a Communicative English Language Teaching (CELT) classroom observation checklist, a Behavior and Instructional Management Scale (BIMS), and a focus group. The findings showed that this group of students have scored low in this subject, that the teacher employs only few aspects of a communicative approach, that the teacher follows an interventionist style regarding classroom management, and that the actual teaching methodology and management strategies applied in class affects negatively in students’ academic performance. Thus, a lesson plan based on the application of communicative approaches was designed and proposed to solve the problems found in this research project and assure students to improve their English academic performance.